Executive summary. Expert consensus statement on the diagnosis and treatment of paediatric pulmonary hypertension. The European Paediatric Pulmonary Vascular Disease Network, endorsed by ISHLT and DGPK. (6th April 2016) - Hansmann, Georg; Apitz, Christian; Abdul-Khaliq, Hashim; Alastalo, Tero-Pekka; Beerbaum, Phillip; Bonnet, Damien; Dubowy, Karl-Otto; Gorenflo, Matthias; Hager, Alfred; Hilgendorff, Anne; Kaestner, Michael; Koestenberger, Martin; et al.
Abstract : The European Paediatric Pulmonary Vascular Disease (PVD) Network is a registered, non-profit organisation that strives to define and develop effective, innovative diagnostic methods and treatment options in all forms of paediatric pulmonary hypertensive vascular disease, including specific forms such as pulmonary arterial hypertension (PAH)-congenital heart disease, pulmonary hypertension (PH) associated with bronchopulmonary dysplasia, persistent PH of the newborn, and related cardiac dysfunction. Methods: The writing group members conducted searches of the PubMed/MEDLINE bibliographic database (1990–2015) and held five face-to-face meetings with votings. Clinical trials, guidelines, and reviews limited to paediatric data were searched using the terms 'pulmonary hypertensioń' and 5–10 other keywords, as outlined in the other nine articles of this special issue. Class of recommendation (COR) and level of evidence (LOE) were assigned based on European Society of Cardiology/American Heart Association definitions and on paediatric data only, or on adult studies that included >10% children. Results: A total of 9 original consensus articles with graded recommendations (COR/LOE) were developed, and are summarised here. The topics included diagnosis/monitoring, genetics/biomarker, cardiac catheterisation, echocardiography, cardiac magnetic resonance/chest CT, associated forms of PH, intensive care unit/ventricular assist device/lung transplantation, and treatment of paediatric PAH. Conclusions: The multipaper expert consensus statement of the European Paediatric PVD Network provides a specific, comprehensive, detailed but practical framework for the optimal clinical care of children with PH.